PROBLEMS AND LESSONS IN FAMINE PREVENTION IN FERGANA PROVINCE (Conferencea, 2022)
In this article, the collapse of the economy as a result of the political crises that began in Russia, the sharp decrease in the supply of grain and other food products from the center to Turkestan, the emergence of famine in the Ferghana Valley as a result of drought, natural disasters, the measures taken by the Soviet authorities to solve the problem, in particular, The fact that the lack of food reserves, the lack of incentives for local producers caused the suffering and death of millions of people, and that the measures to prevent these situations did not have a positive result, are illuminated by the study of archival data and periodical sources.